Estrogens, age, and, neonatal stress: panic disorders and novel views on the contribution of non-medullary structures to respiratory control and CO2 responses - Kinkead, Richard; Ambrozio-Marques, Danuzia; Fournier, Stéphanie; Gagnon, Marianne; Guay, Loralie Mei (Frontiers in Physiology, 2023)
CO2 is a fundamental component of living matter. This chemical signal requires close monitoring to ensure proper match between metabolic production and elimination by lung ventilation. Besides ventilatory adjustments, CO2 can also trigger innate behavioral and physiological responses associated with fear and escape but the changes in brain CO2/pH required to induce ventilatory adjustments are generally lower than those evoking fear and escape. However, for patients suffering from panic disorder (PD), the thresholds for CO2-evoked hyperventilation, fear and escape are reduced and the magnitude of those reactions are excessive. To explain these clinical observations, Klein proposed the false suffocation alarm hypothesis which states that many spontaneous panics occur when the brain’s suffocation monitor erroneously signals a lack of useful air, thereby maladaptively triggering an evolved suffocation alarm system. After 30 years of basic and clinical research, it is now well established that anomalies in respiratory control (including the CO2 sensing system) are key to PD. Here, we explore how a stress-related affective disorder such as PD can disrupt respiratory control. We discuss rodent models of PD as the concepts emerging from this research has influenced our comprehension of the CO2 chemosensitivity network, especially structure that are not located in the medulla, and how factors such as stress and biological sex modulate its functionality. Thus, elucidating why hormonal fluctuations can lead to excessive responsiveness to CO2 offers a unique opportunity to gain insights into the neuroendocrine mechanisms regulating this key aspect of respiratory control and the pathophysiology of respiratory manifestations of PD.